RANCANG BANGUN SISTEM INFORMASI TATA TERTIB SISWA BERBASIS WEB MENGGUNAKAN MODEL USER CENTERED DESIGN - Frizy, Muhammad Firdan; Dwanoko, Yoyok Seby; Agustina, Rini (Department of System Information, 2026)
Student discipline management at MA Mansyaul Ulum is still carried out manually on paper, which has the potential to cause data loss, recording errors, and difficulties in searching for and recapitulating student violations. This condition makes it difficult for students, teachers, discipline officers, and the school to monitor student violations quickly and accurately. Therefore, an information system capable of managing student disciplinary data in an integrated and effective manner is needed. This study aims to design and develop a web-based Student Discipline Information System to facilitate the management, monitoring, and recapitulation of student violation data at MA Mansyaul Ulum. The system was developed using the User-Centered Design (UCD) method to ensure that the system meets user needs. The context of use was determined through interviews with the school. The application was built using the PHP programming language with MySQL as the database. The results of this system development show that the system is capable of displaying student violation and handling data and presenting reports on a daily, weekly, and monthly basis. System testing using the Black Box Testing and User Acceptance Testing (UAT) methods obtained an average score of 96.47%, indicating that the system runs well and is accepted by users.